EVALUATION OF NATURAL ENEMIES IN CONTROLLING OF THE BANANA WEEVIL BORER Cosmopolites sordidus Germar IN WEST SUMATRA - Ahsol Hasyim; Azwana Azwana; Syafril Syafril (Indonesian Agency for Agricultural Research and Development, 2009)
The banana weevil, Cosmopolites sordidus Germar, is an important pest of highland banana and plantain in Africa, but it exists in low densities in presumed area of origin in Southeast Asia such as in Indonesia. This suggests a possible existence of effective co-evolved natural enemies in the origin area of Indonesia, especially West Sumatra. The objectives of this study were: (1) to evaluate banana weevil pest status at selected sites in West Sumatra, (2) to survey parasitoids and predators, and (3) to determine the control potential of the most important natural enemies. Surveys were undertaken in March 2002-August 2003 in five locations in West Sumatra, i.e., Bukittinggi, Sitiung, Pariaman, Pasaman, and Batusangkar. Five farms per site were selected randomly among all farms that contained banana stands of > 0.5 ha. Sampling for banana weevil adults and damage, and for predators was done throughout small banana stands and within a 20 m x 40 m (0.08 ha) subplot on larger farms. Field-collected larvae were taken to the laboratory and reared on corm pieces (3 cm x 3 cm x 3 cm) until pupation. Larvae were collected from pseudostem as well as corm residues. To estimate the abundance of non-social predators, i.e., those other than ants, 10 residues each on each farm were examined from plants that had been harvested 1-4 weeks, 5-8 weeks or 9 or more weeks before our visit to the site. Samples of the different morphospecies were saved in alcohol for later identification. The result showed that the banana weevil incidence was found to be low, 0.6-1.7 adults per trap. Plant damage indices were below 2.2%. We collected and reared 24,360 eggs and 3118 larvae, but no parasitism was detected. Phorids (Megaselia sp.) and drosophilids were recovered from larval rearings, but most likely were scavengers. A complex of predators was detected, the most important of which was the histerid beetles, Plaesius javanus Erichson. In laboratory tests, adults and larvae of P. javanus attacked 75-88% and 38-53% of banana weevil larvae and pupae, respectively. Predatory ants, including species of Myrmicinae, Ponerinae, Formicinae, and Dolichoderinae, were found to be associated with banana plants and residues. Adults of Myopopone castanea Smith (Ponerinae) were directly observed attacking banana weevil larvae in crop residues. The adult banana weevil mortalities caused by the entomopathogen fungi of Beauveria bassiana from Baso, Sungaitarab, Sei Sariek, and Sikabau at highest density (3.2 x 108 spores ml-1) after two weeks were 96.67%, 90.00%, 60.00% and 83.33%, respectively. The high diversity of habitat conditions in which crop-pest-natural enemies systems exist, support the idea that banana weevil population and damage intensity in the study area is low due to active role of natural enemies.